Water balance - stream water level and discharge from Följemaden, outlet-stream-4 - Skogaryd Research Catchment (University of Gothenburg, 2024)
Stream water level measurements and discharge calculations from streams participating in the SITES Water and station base program including a constantly validated stream discharge relation curve. For further information on calculations and installation read COMMENT in the header of the data set, which guides to related document.
Skogaryd Research Catchment (2024). Water balance - stream water level and discharge from Följemaden, outlet-stream-4, 2012-01-01–2014-01-14 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/e3_E26Wi2VdAZaEa2wQQtgVu
Keywords: Skogaryd Research Catchment; Discharge; Inland waters; Stream; Water level gauges; Time instant; Time instant; Stream level; Stream level; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap